Understanding the factors influencing pharmacokinetics of tacrolimus - V., Sivakumar; M., Rakshna; M. S., Soorya; S., Pranesh (International Journal of Research in Medical Sciences, 2024)
Tacrolimus, a potent calcineurin inhibitor integral to immunosuppressive regimens, exhibits complex pharmacokinetics influenced by diverse factors and understanding these factors is crucial for safety, efficacy and dose optimisation. Genetic variations, particularly in CYP3A enzyme systems and P- Glycoprotein, contribute significantly to inter-individual variability in tacrolimus metabolism. Polymorphisms in these systems alter drug bioavailability, impacting clinical outcomes. Ethnicity further compounds this variability, with distinct genetic profiles leading to differential drug responses. Notably, black patients, often characterized by CYP3A5 expressor status, may have higher drug clearance. Age-related changes in tacrolimus clearance highlights the discrepancies in elderly and paediatric populations. On the other hand, prediction of gender-specific differences is difficult due to lack of evidence. Body composition, specifically variations in fat and muscle mass, significantly impacts drug distribution and clearance. Obesity, associated with altered CYP3A activity, results in decreased drug clearance, emphasizing the importance of accounting for body composition in dosing calculations. Pregnancy -induced physiological changes affect tacrolimus absorption, distribution, metabolism, and excretion, necessitating careful monitoring and dose adjustments in pregnant individuals. Dietary factors and drug interactions, particularly with CYP3A4 and P-glycoprotein, further contribute to the intricate web of variables influencing tacrolimus pharmacokinetics. In conclusion, this review sheds light on the multifaceted factors influencing tacrolimus pharmacokinetics, providing essential insights for clinicians to tailor individualized dosing regimens and enhance therapeutic efficacy while minimizing the risk of adverse events.